Cardiovascular Events with Finerenone in Kidney Disease and Type 2 Diabetes - Pitt, Bertram; Filippatos, Gerasimos; Agarwal, Rajiv; Anker, Stefan D; Bakris, George L; Rossing, Peter; Joseph, Amer; Kolkhof, Peter; Nowack, Christina; Schloemer, Patrick; Ruilope, Luis M (The New England journal of medicine, 2021)
In this double-blind trial, patients with stage 1 to 4 chronic kidney disease and type 2 diabetes were randomly assigned to receive finerenone or placebo. Finerenone treatment was superior with regard to the primary composite outcome of death from cardiovascular causes, nonfatal myocardial infarction, nonfatal stroke, or hospitalization for heart failure.